2000
DOI: 10.1034/j.1399-0012.2000.140505.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of alloantibodies against non‐HLA antigens in kidney transplantation by flow cytometry

Abstract: The presence of alloantibodies against human leucocyte antigen (HLA)-I and HLA-II antigens has been associated with hyperacute and accelerated graft rejections. However, occasionally these rejections occur in patients without donor-specific anti-HLA antibodies, suggesting the presence of other antigenic complexes that are shared by the graft and other cell populations. Usually, these antibodies are not routinely studied and their role in graft rejection is poorly understood. For this reason, we tested, by flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The targets for antibodies that cause late graft failure could be minor histocompatibility antigens, or PRA reactivity may indicate a general state of heightened immune responsiveness as a result of previous alloimmunization. Anti-endothelium/monocyte antibodies have been shown to be associated with hyperacute rejection, although this is probably rare (33). Two previous studies showed higher anti-endothelial cell antibodies in patients with a failed renal transplant as a result of chronic rejection compared with patients with functioning allografts (34,35).…”
Section: Type Of Antibody and Its Effect On Allograft Outcomementioning
confidence: 99%
“…The targets for antibodies that cause late graft failure could be minor histocompatibility antigens, or PRA reactivity may indicate a general state of heightened immune responsiveness as a result of previous alloimmunization. Anti-endothelium/monocyte antibodies have been shown to be associated with hyperacute rejection, although this is probably rare (33). Two previous studies showed higher anti-endothelial cell antibodies in patients with a failed renal transplant as a result of chronic rejection compared with patients with functioning allografts (34,35).…”
Section: Type Of Antibody and Its Effect On Allograft Outcomementioning
confidence: 99%
“…Fakat HLA identik nakiller sonrası hastaların rejeksiyon episodları sonucu graftlarını kaybetmesi HLA antijenlerinin dışında başka immünolojik faktörlerin de etkili olabileceğini düşündürmüştür. [25] Graftversus-host hastalığı gelişimi üzerine mHAg uyumsuzluğunun etkisi en iyi, HLA tam uyumlu kardeş çiftleriyle yapılan çalışmalarla anlaşılmıştır. [4] HA-1 lokusundaki uyumsuzluğun, aGVHH gelişimi için potansiyel bir risk faktörü olduğu Goulmy ve ark.nın [26] yaptığı çalışmalar-da belirtilmiş ve ayrıca aGVHH'li hastaların periferik kanlarında, HA-1 spesifik sitotoksik T lenfositlerinin yükseldiği de bildirilmiştir.…”
Section: Discussionunclassified
“…A strong correlation between the development of alloantibodies to mismatched HLAs and poor graft outcomes has been reported by many investigators (Adeyi et al 2005;BaidAgrawal & Frei, 2007;Mujtaba et al, 2010;. Recipients of perfectly matched kidney transplants generally survive longer and do not frequently develop rejection; however, 2-5% of zero HLA-mismatched kidney recipients lose their grafts due to HAR or AMR (Rodriguez et al, 2000). These graft failures can be caused by HLA allele-specific antibodies and/or non-HLA antibodies (Ferry et al, 1997;Grandtnerova et al, 2008;Lomago et al, 2010;Lucchiari et al, 2000;Perrey et al, 1998;Sumitran-Karuppan et al, 1997).…”
Section: Anti-endothelial Cells (Ec) Antibodiesmentioning
confidence: 99%
“…The vascular endothelium of transplanted kidneys and other organs is the first line of defense between the allograft and the host immune system. Similar to classical MHC antigens, the non-HLAs represent immune system targets, and AECAs appear to be clinically important as a potential risk factor for AMR (Han et al, 2009;Pober et al, 1996;Rodriguez et al, 2000;Vasilescu et al, 2004;Yard et al, 1993;Vanderwoude et al, 1995). FCCM analysis using peripheral blood EC for the detection of AECAs has been recently described.…”
Section: Anti-endothelial Cells (Ec) Antibodiesmentioning
confidence: 99%